2018
DOI: 10.1007/s13337-018-0459-z
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and factors influencing varicella infections in tropical countries including Sri Lanka

Abstract: Varicella zoster virus (VZV) infections occur worldwide but the epidemiology differs between different geographical regions. Epidemiology of varicella is partly understood in tropical and subtropical regions. Various hypotheses showing differences in exposure rates in different age groups have been proposed. Exposure to VZV during late childhood or adolescent stage causes high morbidity, especially in high school children, university students and young work force in tropical nations. Exposure to VZV infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…Consequently, high IgG seroprevalence indicates most likely high virus circulation levels. Several studies suggested that infection occurs in late adolescence or early adulthood [ 71 , 74 , 75 ] and earlier in temperate climates [ 132 ]. Previous studies indicated that temperate weather conditions might favor virus transmission, explaining earlier immunity in these countries [ 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, high IgG seroprevalence indicates most likely high virus circulation levels. Several studies suggested that infection occurs in late adolescence or early adulthood [ 71 , 74 , 75 ] and earlier in temperate climates [ 132 ]. Previous studies indicated that temperate weather conditions might favor virus transmission, explaining earlier immunity in these countries [ 133 , 134 ].…”
Section: Discussionmentioning
confidence: 99%
“…Others suggested that a tropical humid climate interferes with virus stability and that virus transmission patterns differ between the different virus variants. Supposedly because of lower population densities, virus circulation in rural settings of tropical countries is low [ 132 ]. While the high seroprevalence rates in adults suggest that the risk of primary infection during pregnancy is small, vaccination of vulnerable groups such as women of reproductive age, people with chronic diseases, children and HCW should be further discussed.…”
Section: Discussionmentioning
confidence: 99%
“…In temperate regions, varicella is a disease of preschool and school-age children (Socan et al, 2010;van Rijckevorsel et al, 2012). In tropical regions, varicella typically occurs at a later age (Daulagala & Noordeen, 2018;Mandal et al, 1998) with many cases in adolescents and adults who are at risk of developing more severe disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The epidemiology of Varicella zoster is incompletely understood in tropical and subtropical regions, though various hypotheses have been proposed to explain the different age distribution. Climatic factors, socioeconomic conditions, mobility and cultural practices seem to play a role in the differences in the exposure rates to Varicella zoster virus infection in the tropics (Daulagala & Noordeen, 2018). The age distribution of varicella in tropical regions varies with place of residence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, there are limitations in the registration of cases of varicella and herpes zoster, which leads to a lack of knowledge of infection and disease patterns [8]. Environmental factors, socioeconomic conditions, migration, and cultural practices seem to influence the differences in rates of exposure to VZV and consequent seroprevalence [17]. The age of the pregnant women, area of residence, number of deliveries, and occupation have been reported as conditions that influence the seroprevalence of varicella in different regions of the world [18,19].…”
Section: Introductionmentioning
confidence: 99%